Ameliorative effects of dietary selenium against cadmium toxicity on production performance and egg quality in laying hens - Lu Xing; Runxiang Zhang; Rixin Gong; Xiaotao Liu; Jun Bao; Jianhong Li (Ecotoxicology and Environmental Safety, 2022)
In order to reveal the influences of supplemented dietary selenium (Se) on the suppressive effect of cadmium (Cd) toxicity on performance and egg properties of laying hens, the effects of co-treatment Se and Cd on the performance, egg quality, levels of amino acids and the antioxidant capacity of egg and serum were investigated. A total of 128 31-week-old laying hens were randomly distributed in four treatments, which were fed with the basic diet (0.2 mg/kg Se and 0.08 mg/kg Cd), and the basic diet with Se (1.1 mg/kg Se and 0.08 mg/kg Cd), Cd (0.2 mg/kg Se and 92.1 mg/kg Cd) and Se+Cd for 13 weeks, respectively. Hens supplemented with Cd led to an impairment on production performance and egg quality with decreased egg production (EP), egg mass (EM), feed intake (FI), eggshell color, eggshell thickness, yolk color, albumen height and haugh unit and increased the feed conversion ratio (FCR) (p < 0.05). Cd treatment decreased the contents of cysteine (Cys), histidine (His), lithium (Li), aluminum (Al), chromium (Cr), manganese (Mn), nickel (Ni), zinc (Zn), arsenic (As), Se, strontium (Sr), stannum (Sn), mercury (Hg) and thallium (Tl) and increased the contents of isoleucine (Ile) and Cd (p < 0.05). Cd destroyed the egg yolk and serum redox states with the increased concentration of malondialdehyde (MDA) and the decreased activities of superoxide dismutase (SOD) and glutathione peroxidase (GPx) (p < 0.05). The expression levels of ovarian apoptotic genes (protein 53, Caspase9, Cytochrome c and Bcl-2 associated X protein) increased, and B-cell lymphoma 2 (Bcl-2) expression decreased in the Cd group (p < 0.05). Feeding Se significantly alleviated Cd-induced toxicity on performance and egg quality. Se+Cd treatment restored the balance between oxidation and antioxidant systems and modulated the elements' homeostasis and alleviated the changes in apoptotic-related genes expression levels. Se could alleviate the Cd toxicity to laying hens and their eggs but could not counteract all negative effects of Cd.